A report on the mass mortality of the farmed Japanese scallop, Patinopecten yessoensis on the Korean coasts of the East Sea - Jo, Qtae; Kim , Su-Kyoung; Chu, Lee; Rahman, Mohammad Mustafizur; Chae, Sung Lee; Bong-se, Oh (The Malacological Society of Korea, 2009)
Unexpected mass mortality has been one of the drawbacks in front of the stable production of Japanese scallop (Patinopecten yessoensis) on the Gangwon coasts of the East Sea. The preliminary data from our routine observation revealed that the mortality appeared to be related to variation of water temperature in the farming site and the degree of the mortality was dependent on scallop strain. The present study performed to verify the preliminary findings exhibited that the mortality was closely related to daily temperature variation rather than monthly variation. Daily temperature variation was particularly damageable to the scallop during the temperature elevation period. Scallops from hatchery seeds (Chinese strain) were more tolerant against the temperature variation over those from wild seeds. The hatchery scallop gain of the temperature tolerance was probably due to their larval experience to higher temperature in the hatchery as well as their maternal genetic acclimation to upper temperature extreme of the Chinese environment which was recently found.